Digitalisasi Pendataan Balita Posyandu Kasuari Dusun Sono untuk Meningkatkan Kualitas Monitoring dan Pelaporan Kesehatan Balita: - Angelica, Era Riece Swany; Jong, Jek Siang; Budi Santoso, Halim (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Public Health Services Kasuari is located in Sono Village, Wedomartani, Sleman, Yogyakarta. This health service has regular health check services to monitor and record baby’s growth every 35 days. Some volunteers write the health record manually using a health card which was prone to damage or loss. Through a community empowerment program, we offer a web-based information system, named posyanduku.net, for recording baby’s health record. The purpose of this information system is to replace a physical card, reducing the risk of losing and damaging the health record. Furthermore, it can increase the accessibility of the health record by providing access to parents and other stakeholders. The data entry starts from the volunteers to entry health records during the health check process. Parents of toddlers can monitor their child’s growth online. After developing posyanduku.net, the team held socialization to the users, such as volunteers and parents. We also provide a user manual to help users to learn on how to use the system. To assess its functionality and effectiveness, we conducted an evaluation by distributing a questionnaire to 16 participants (6 volunteers and 10 parents). According to the questionnaire response, we found that either parents and volunteers perceive that the system is easy to use and useful to administer the toddlers health record. Keywords — public health service, health record, toddlers health record, information system, healthcare information